الآثار المتبادلة بين التجارة والبيئة (دراسة تحليلية حول المعايير البيئية والنفاذ إلى الأسواق العالمية في سورية ) - محمود, حبيب; تفاحة, أيهم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
أصبحت موضوعات التجارة والبيئة تثير جدلاً كبيراً لدى الكثير من البحوث والدراسات، وفي أماكن صنع القرار، خاصّة في ظل تزايد عمليات تحرير التجارة الدولية، وزيادة تدفقات الاستثمار الأجنبي المباشر والاتفاقيات الدولية من جهة، وتعاظم المشكلات البيئية وانعكاساتها الاقتصادية والاجتماعية في عالم اليوم من جهة أخرى. ويتركز الجدل بشكل أساسي من خلال: أثر حركة التجارة على سلامة البيئة، وأثر المعايير البيئية على حركة التجارة والتنافسية. إن جوهر قضايا البيئة ذات الصلة بالتجارة هو كيفية تحقيق توازن بين الحاجة إلى التنمية وبين الحاجة إلى الحفاظ على البيئة، والذي يأتي من خلال رسم سياسات اقتصادية تنموية تراعي البعد البيئي وتحقق التنمية المستدامة بأبعادها المختلفة. ونظراً لأهمية وحيوية الموضوع جاء هذا البحث ليسلط الضوء على أهمية دراسة العلاقة بين التجارة والبيئة، ودراسة أهمية تطبيق المعايير البيئية في تسهيل نفاذ المنتجات السورية إلى الأسواق العالمية، خاصّة إلى أسواق الاتحاد الأوروبي والأسواق الأمريكية التي تطبق معايير بيئية متشددة على الواردات من جميع الدول. The topics of trade and environment become raises great controversy with a lot of research and studies, and in places of decision-making, especially in light of the increasing liberalization of international trade, and increased flows of foreign direct investment and international conventions on the one hand, and growing environmental problems in today's world on the other. The focus of the controversy mainly through: the impact of trade on the environment, and the impact of environmental standards on the movement of trade and competitiveness. The essence of the environmental issues related to trade is how to achieve a balance between the need for development and preservation of the environment, which comes through economic development policies take into account the environmental dimension of sustainable development and achieve its various dimensions. Given the importance and vitality of the subject of this research was to highlight the importance of studying the relationship between trade and environment, and to study the importance of applying environmental standards to facilitate the entry into force of Syrian products to global markets, especially to the markets of the European Union and U.S. markets that apply stricter environmental standards on imports from all countries.